2015
DOI: 10.1118/1.4903892
|View full text |Cite
|
Sign up to set email alerts
|

Markerless motion tracking of lung tumors using dual‐energy fluoroscopy

Abstract: This work indicates the potential for markerless tumor tracking utilizing DE fluoroscopy. With DE imaging, the algorithm showed improved detectability vs SE fluoroscopy and was able to accurately track the tumor in nearly all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 50 publications
0
86
0
Order By: Relevance
“…Improved contrast of lung lesions after DE subtraction, resulting in significant improvement in markerless tumor localization, has been reported by several groups [16][17][18][19]. In this study, we evaluate the feasibility of markerless tumor tracking through the implementation of DE subtraction imaging into the current clinical RTTT workflow, using the implanted fiducials as a benchmark.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Improved contrast of lung lesions after DE subtraction, resulting in significant improvement in markerless tumor localization, has been reported by several groups [16][17][18][19]. In this study, we evaluate the feasibility of markerless tumor tracking through the implementation of DE subtraction imaging into the current clinical RTTT workflow, using the implanted fiducials as a benchmark.…”
Section: Introductionmentioning
confidence: 75%
“…one imaging angle, a normalized cross-correlation (NCC) algorithm with an ad-hoc 200 Â 200 pixel region-of-interest (ROI), including sufficient patient anatomy, was applied to find the best-matching HE image for each LE image [17]. After LE-HE image matching, all LE-HE image couples were allocated to their respective breathing phase (inhale, exhale, maximum inhale and maximum exhale) based on the amplitude of the external breathing signal and synchronized timestamps.…”
Section: Off-line Correlation and Subtractionmentioning
confidence: 99%
“…Energies for DE imaging were selected based on previous studies where image quality and dose were optimized. 30,[43][44][45] A prior study demonstrated that the estimated mean dose at the skin per DE image pair was approximately 0.44 6 0.03 mGy, comparable with the expected skin dose from conventional SE imaging. 30 Image pairs were acquired once per treatment fraction with a maximum of five sets per patient.…”
Section: Image Acquisitionmentioning
confidence: 96%
“…Our previous study showed that the average displacement between the two physician's ground truth co-ordinates was 1.0 6 0.8 mm. 44 If more physicians were involved in the process, a more precise determination of ground truth may be possible. Additionally, this study uses a template-matching algorithm that is not yet commercially available and therefore this system cannot yet be employed in clinics without access to the software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation